Moderation of Good Corporate Governance: Earnings Management and Firm Value Against Company Performance - Ibrahim Ibrahim; Eldi Eldi; Amir Amir; Bunyamin Bunyamin (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
We conducted this study to analyze and examine the influence of earnings management and firm value on firm performance. We also use the variable good corporate governance as a moderating variable to test both. The proxy used for earnings management is the modified jones, firm value using Tobins'Q, financial performance with Return on Assets (ROA), and the GCG proxy taken by researchers, namely the audit committee. The research uses a descriptive method using multiple linear regression analysis test equipment. Data collection was carried out using secondary data on food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange. From the withdrawal of the target population, only 14 companies were obtained that met the criteria. The results of this study indicate that the company's value partially does not affect the company's financial performance, but earnings management affects the company's performance; earnings management moderated by good corporate governance affects the company's financial performance and firm value.